Design of polar self-assembling lactic acid derivatives possessing submicrometre helical pitch - Bubnov, Alexej; Vacek, Cyril; Czerwiński, Michał; Vojtylová, Terezia; Piecek, Wiktor; Hamplová, Věra (Beilstein Journal of Nanotechnology, 2018)
Several new lactic acid derivatives containing the keto linkage group far from the chiral part and short alkyl chains have been synthesized and characterised by polarising optical microscopy, differential scanning calorimetry, as well as electro-optic and dielectric spectroscopy. The materials possess a self-assembling behaviour on the nanoscale level as they form polar smectic liquid crystalline mesophases, namely the orthogonal paraelectric SmA* and the tilted ferroelectric SmC* phases, in a broad temperature range down to room temperature. A short helical pitch (≈120–320 nm), relatively high spontaneous polarisation (≈150 nC/cm2) and reasonable tilt angle values have been determined within the temperature range of the tilted ferroelectric SmC* phase. The obtained results make the new materials useful for the advanced mixture design and for further utilisation in electro-optic devices based on the deformed helix ferroelectric effect.
Keywords: ferroelectric liquid crystal; keto group; self-assembly on the nanoscale; soft ferroelectrics; submicrometre helical pitch length

(untitled) - Lagerwall, J. P. F.; Scalia, G. (Curr. Appl. Phys., 2012)

(untitled) - Lagerwall, J. P. F.; Giesselmann, F. (ChemPhysChem, 2006)

Ferroelectric and Antiferroelectric Liquid Crystals - Lagerwall, S. T. (Wiley-VCH Verlag GmbH, 2007)

(untitled) - Dąbrowski, R.; Kula, P.; Raszewski, Z.; Piecek, W.; Otón, J. M.; Spadło, A. (Ferroelectrics, 2010)

Liquid Crystal Photonics (Engineering Tools, Techniques and Tables) - Chigrinov, V. G. (Nova Science Publishers, Inc., 2014)

(untitled) - Pramanik, A.; Das, M. K.; Das, B.; Hamplová, V.; Kašpar, M.; Bubnov, A. (Phase Transitions, 2015)

(untitled) - Szczuciński, Ł.; Dąbrowski, R.; Urban, S.; Garbat, K.; Filipowicz, M.; Dziaduszek, J.; Czerwiński, M. (Liq. Cryst., 2015)

(untitled) - Kurp, K.; Czerwiński, M.; Tykarska, M. (Liq. Cryst., 2015)

(untitled) - Bubnov, A.; Novotná, V.; Hamplová, V.; Kašpar, M.; Glogarová, M. (J. Mol. Struct., 2008)

(untitled) - Catalano, D.; Domenici, V.; Marini, A.; Veracini, C. A.; Bubnov, A.; Glogarová, M. (J. Phys. Chem. B, 2006)

(untitled) - Novotná, V.; Hamplová, V.; Bubnov, A.; Kašpar, M.; Glogarová, M.; Kapernaum, N.; Bezner, S.; Giesselmann, F. (J. Mater. Chem., 2009)

(untitled) - Bubnov, A.; Kašpar, M.; Hamplová, V.; Glogarová, M.; Samaritani, S.; Galli, G.; Andersson, G.; Komitov, L. (Liq. Cryst., 2006)

(untitled) - Bubnov, A.; Domenici, V.; Hamplová, V.; Kašpar, M.; Zalar, B. (Polymer, 2011)

(untitled) - Garić, M.; Bubnov, A.; Novotná, V.; Kašpar, M.; Hamplová, V.; Obadović, D. Ž.; Glogarová, M. (Liq. Cryst., 2005)

(untitled) - Malik, P.; Raina, K. K.; Bubnov, A.; Choudhary, A.; Singh, R. (Thin Solid Films, 2010)

(untitled) - Brombach, F.; Neudörfl, J. M.; Blunk, D. (Mol. Cryst. Liq. Cryst., 2011)

(untitled) - Wu, S.-L.; Hsu, H.-N. (Liq. Cryst., 2007)

(untitled) - Navailles, L.; Nguyen, H. T.; Barois, P.; Destrade, C.; Isaert, N. (Liq. Cryst., 1993)

(untitled) - Otterholm, B.; Alstermark, C.; Flatischler, K.; Dahlgren, A.; Lagerwall, S. T.; Skarp, K. (Mol. Cryst. Liq. Cryst., 1987)

(untitled) - Bubnov, A.; Novotná, V.; Pociecha, D.; Hamplová, V.; Kašpar, M. (Phase Transitions, 2012)

(untitled) - Bubnov, A.; Podoliak, N.; Hamplová, V.; Tomášková, P.; Havlíček, J.; Kašpar, M. (Ferroelectrics, 2016)

(untitled) - Piecek, W.; Bubnov, A.; Perkowski, P.; Morawiak, P.; Ogrodnik, K.; Rejmer, W.; Żurowska, M.; Hamplová, V.; Kašpar, M. (Phase Transitions, 2010)

(untitled) - Obadović, D. Ž.; Vajda, A.; Garić, M.; Bubnov, A.; Hamplová, V.; Kašpar, M.; Fodor-Csorba, K. (J. Therm. Anal. Calorim., 2005)

(untitled) - Novotná, V.; Hamplová, V.; Kašpar, M.; Glogarová, M.; Bubnov, A.; Lhotáková, Y. (Ferroelectrics, 2004)

(untitled) - Bobrovsky, A.; Shibaev, V.; Elyashevitch, G.; Rosova, E.; Shimkin, A.; Shirinyan, V.; Bubnov, A.; Kašpar, M.; Hamplová, V.; Glogarová, M. (Liq. Cryst., 2008)

(untitled) - Bubnov, A.; Hamplová, V.; Kašpar, M.; Vajda, A.; Stojanović, M.; Obadović, D. Ž.; Éber, N.; Fodor-Csorba, K. (J. Therm. Anal. Calorim., 2007)

(untitled) - Iwan, A.; Sikora, A.; Hamplová, V.; Bubnov, A. (Liq. Cryst., 2015)

(untitled) - Shukla, R. K.; Raina, K. K.; Hamplová, V.; Kašpar, M.; Bubnov, A. (Phase Transitions, 2011)

(untitled) - Bubnov, A.; Iwan, A.; Cigl, M.; Boharewicz, B.; Tazbir, I.; Wójcik, K.; Sikora, A.; Hamplová, V. (RSC Adv., 2016)

(untitled) - Novotná, V.; Vejpravová, J.; Hamplová, V.; Prokleška, J.; Gorecka, E.; Pociecha, D.; Podoliak, N.; Glogarová, M. (RSC Adv., 2013)

(untitled) - Iwan, A.; Boharewicz, B.; Tazbir, I.; Hamplová, V.; Bubnov, A. (Solid-State Electron., 2015)

(untitled) - Kašpar, M.; Bubnov, A.; Sedláková, Z.; Stojanović, M.; Havlíček, J.; Obadović, D. Ž.; Ilavsky, M. (Eur. Polym. J., 2008)

(untitled) - Piecek, W.; Dąbrowski, R.; Morawiak, P.; Żurowska, M.; Jaroszewicz, L. (Phase Transitions, 2012)

(untitled) - Murauski, A. A. (Ferroelectrics, 2006)

(untitled) - Yoshizawa, A.; Nishiyama, I.; Fukumasa, M.; Hirai, T.; Yamane, M. (Jpn. J. Appl. Phys., Part 2, 1989)

(untitled) - Petrov, V. F. (Mol. Cryst. Liq. Cryst., 2005)

(untitled) - Hamplová, V.; Bubnov, A.; Kašpar, M.; Novotná, V.; Glogarová, M. (Liq. Cryst., 2003)

(untitled) - Stojanović, M.; Obadović, D. Ž.; Bubnov, A.; Hamplová, V.; Kašpar, M. (AIP Conf. Proc., 2007)

(untitled) - Hamplová, V.; Bubnov, A.; Kašpar, M.; Novotná, V.; Pociecha, D.; Glogarová, M. (Liq. Cryst., 2003)

(untitled) - Hamplová, V.; Bubnov, A.; Kašpar, M.; Novotná, V.; Lhotáková, Y.; Glogarová, M. (Liq. Cryst., 2003)

(untitled) - Kesaev, V. V.; Kiselev, A. D.; Pozhidaev, E. P. (Phys. Rev. E, 2017)

(untitled) - Kotova, S. P.; Samagin, S. A.; Pozhidaev, E. P.; Kiselev, A. D. (Phys. Rev. E, 2015)

(untitled) - Brodzeli, Z.; Silvestri, L.; Michie, A.; Guo, Q.; Pozhidaev, E. P.; Chigrinov, V.; Ladouceur, F. (Liq. Cryst., 2013)

(untitled) - Pozhidaev, E. P.; Vashchenko, V. V.; Mikhailenko, V. V.; Krivoshey, A. I.; Barbashov, V. A.; Shi, L.; Srivastava, A. K.; Chigrinov, V. G.; Kwok, H. S. (J. Mater. Chem. C, 2016)

(untitled) - Kiselev, A. D.; Pozhidaev, E. P.; Chigrinov, V. G.; Kwok, H.-S. (Phys. Rev. E, 2011)

(untitled) - Guo, Q.; Brodzeli, Z.; Silvestri, I.; Srivastava, A. K.; Pozhidaev, E. P.; Chigrinov, V. G.; Kwok, H. S. (Photonics Lett. Pol., 2013)

(untitled) - Kurp, K.; Czerwiński, M.; Tykarska, M.; Bubnov, A. (Liq. Cryst., 2017)

(untitled) - Bubnov, A.; Tykarska, M.; Hamplová, V.; Kurp, K. (Phase Transitions, 2016)

(untitled) - Tykarska, M.; Czerwiński, M. (Liq. Cryst., 2016)

(untitled) - Chełstowska, A.; Czerwiński, M.; Tykarska, M.; Bennis, N. (Liq. Cryst., 2014)

(untitled) - Kohout, M.; Bubnov, A.; Šturala, J.; Novotná, V.; Svoboda, J. (Liq. Cryst., 2016)

(untitled) - Taniguchi, H.; Ozaki, M.; Yoshino, K.; Satoh, K.; Yamasaki, N. (Ferroelectrics, 1988)

(untitled) - Bubnov, A.; Domenici, V.; Hamplová, V.; Kašpar, M.; Veracini, C. A.; Glogarová, M. (J. Phys.: Condens. Matter, 2009)

(untitled) - Bubnov, A.; Kašpar, M.; Novotná, V.; Hamplová, V.; Glogarová, M.; Kapernaum, N.; Giesselmann, F. (Liq. Cryst., 2008)

Proceedings of the SPIE 5565, XV Conference on Liquid Crystals - Bubnov, A. M.; Glogarová, M.; Semenova, Y.; Panarin, Y.; Kašpar, M.; Hamplová, V. (Properties of new polar liquid crystalline materials with the keto group and different number of lactate units, 1.9.2004)

(untitled) - Lagerwall, J. P. F.; Saipa, A.; Giesselmann, F.; Dąbrowski, R. (Liq. Cryst., 2004)

(untitled) - Fitas, J.; Marzec, M.; Kurp, K.; Żurowska, M.; Tykarska, M.; Bubnov, A. (Liq. Cryst., 2017)

(untitled) - Tykarska, M.; Dąbrowski, R.; Czerwiński, M.; Chełstowska, A.; Piecek, W.; Morawiak, P. (Phase Transitions, 2012)

(untitled) - Beresnev, L. A.; Chigrinov, V. G.; Dergachev, D. I.; Poshidaev, E. P.; Fünfschilling, J.; Schadt, M. (Liq. Cryst., 1989)

(untitled) - Takezoe, H.; Kondo, K.; Fukuda, A.; Kuze, E. (Jpn. J. Appl. Phys., Part 2, 1982)

Smectic and Columnar Liquid Crystals - Goodby, J. W.; Collings, P. J.; Kato, T.; Tschierske, C.; Gleeson, H. F.; Raynes, P. (Wiley-VCH Verlag &Co. KGaA, 2014)

(untitled) - Raszewski, Z.; Kędzierski, J.; Perkowski, P.; Piecek, W.; Rutkowska, J.; Kłosowicz, S.; Zieliński, J. (Ferroelectrics, 2002)